2012
DOI: 10.1007/s00330-012-2442-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of microwave versus radiofrequency ablation for treatment of small hepatocellular carcinoma: experimental and clinical studies

Abstract: MW ablation using a modified cooled-shaft antenna produces a larger ablation zone than RF ablation, with an efficacy similar to RF ablation in local tumour control. MW ablation is a safe and promising treatment of sHCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 23 publications
6
112
1
2
Order By: Relevance
“…The authors considered a high probability of long-term survival of patients with a single lesion ≤4.0 cm in maximum diameter and Child-Pugh class A cirrhosis. Numerous studies have compared MWA with RFA for treating HCC and found similar disease-free survival, cumulative survival, and complication rates in the two groups [68,69,70,71,72,73,74]. However, so far, only one RCT [68] has compared the efficacy of MWA with that of RFA, in a series of 72 patients (36 RFA/36 MWA) with equivalent background demographics and mean tumor sizes.…”
Section: Local Ablative Therapymentioning
confidence: 99%
“…The authors considered a high probability of long-term survival of patients with a single lesion ≤4.0 cm in maximum diameter and Child-Pugh class A cirrhosis. Numerous studies have compared MWA with RFA for treating HCC and found similar disease-free survival, cumulative survival, and complication rates in the two groups [68,69,70,71,72,73,74]. However, so far, only one RCT [68] has compared the efficacy of MWA with that of RFA, in a series of 72 patients (36 RFA/36 MWA) with equivalent background demographics and mean tumor sizes.…”
Section: Local Ablative Therapymentioning
confidence: 99%
“…Microwave ablation (MWA) is also utilised to generate thermal ablation. New devices have a greater burn area with a more consistent penumbra when compared to RFA [95,96]. These treatments are likely to have an evolving role in the future either in combination with resection or in isolation [97].…”
Section: Operative Approachmentioning
confidence: 99%
“…[7] Although energy delivery was underpowered with respect to the maximum power output of the system, MCT yielded ablation areas comparable to those previously reported by other authors who performed MCT using a power output of 100 W and a 14-gauge cooled shaft antenna without choke device. [8] As the minichoked MWA system can also use a 14-gauge antenna with a power output of 100 W, it is hypothesizable that ablation areas even larger than those obtained in the above-mentioned in vivo comparison between MCT and RFA could be achieved using the maximum power output. Indeed, we treated some HCCs and liver metastases measuring up to 7 cm × 6 cm, performing two insertions of a 14-gauge minichoked antenna and using a power output of 90 W for a total ablation time of 20 min, achieving coagulation areas measuring up to 10 cm × 7 cm [ Figures 1 and 2].…”
Section: To the Editormentioning
confidence: 99%